Does It Have A Transportation Infrastructure Increasing Regional Economic Growth on Indonesia? (Spatial Spillover Effect Analysis) - Ahmad Sandi Nurmansyah; Uka Wikarya (PT Mattawang Mediatama Solution, 2023)
This study aims to analyze the effect of transportation infrastructure on economic growth in 33 provinces in Indonesia by using spatial panel data. Spatial panel data combines spatial (spatial) and time (panel) dimensions in its analysis. Spatial panel data can accommodate heterogeneity between provinces and spatial autocorrelation in the model. The model used in this study is the Spatial Durbin Model (SDM), which includes the effect of spatial interaction between the dependent and independent variables and the lag of the independent variable. The study results show that transportation infrastructure, including capital accumulation, labor, length of national roads, ship visits to ports, and airport loading and unloading, positively and significantly affects economic growth in a province and its neighboring provinces through spatial interactions. However, the increase in capital accumulation and the length of national roads in neighboring provinces has a negative and significant effect on economic growth in a province. This research recommends several policies to enhance the development of transportation infrastructure in Indonesia, such as encouraging cooperation between the government and the private sector, increasing the availability and quality of the workforce, and improving the existing transportation infrastructure. Transportation infrastructure development must focus on connectivity, quality, capacity, equity, and inclusiveness between islands and regions to increase collaboration, efficiency, reliability, and prosperity in the regional economy.